Formulation and evaluation of Adhulsa lozenges for pediatric patients - Khaladkar, Atharva Sanjay; Avalaskar, Amruta; Bharati, Pranoti; Honkalas, Kiran (Journal of Drug Delivery and Therapeutics, 2019)
WHO estimates that 235 million people currently suffer from asthma. WHO has recognized herbal medicines as an essential building block for primary health care of vast countries like India. In India the number of children suffering from asthma is increasing. Asthma is the chronic diseases of the bronchi which require continuous medical care. Appropriate management of asthma can enable people to enjoy a good quality of life. Many synthetic and traditional medicines are used in the treatment. Herbal formulations have been used by mankind for the cure and treatment of various diseases and are still popular to a large extend. Justicia adhatoda has been used to treat respiratory and other allergic conditions since years. Vasicine is the main active ingredient of Justicia adhatoda. It has been used in the ayurvedic system of medicine in the treatment of various ailments of respiratory tract both in children and adults. Juice of Adulsa is generally recommended for use. Formulations containing Justicia adhatoda are available in the market, which are syrups or liquid orals. Lozenges are palatable solid unit dosage form administrated in the oral cavity. The study aims in formulation and evaluation of sweet hard candy lozenges using medicinal plant extract especially for administration to pediatric patients for better patient compliance using juice of vasaka leaves. Keywords: Asthma, Traditional medicines, Justicia adhatoda, Vasicine